Data-Driven Platform Framework for Digital Whole-Process Expressway Construction Management - Chen, Shu-Yang; Zhang, Jing-Xiao; Ni, Qi-Chang; Skitmore, Martin; Ballesteros-Pérez, Pablo; Ke, Yong-Jian; Zuo, Jian; Sun, Hao-Jie (Frontiers in Neuroscience, 2022)
As the world’s population and industries continue to develop, expressways are rapidly becoming one of the major types of infrastructure construction projects, particularly in China. To increase the speed and efficiency of their construction, information management is being gradually intro-duced into the construction process. However, progress is limited due to the complexity of ex-pressway engineering and application limitations of information technology. Design and delivery are still dominated by paper files, and the management of test and inspection data is still relatively extensive. Research to date into digital expressway construction has been piecemeal and frag-mented with a lack of research related to the whole construction process and a data-centric infor-mation management system yet to be realized. In response, through literature research and semi-structured interviews, the framework of a data-driven digital whole-process highway construction management platform was determined. A whole process management platform was established according to the framework, and the functional application of the proposed platform was ex-plained through a case. This not only lays the theoretical foundation for research into the whole process of expressway digitalization, but also provides data-centric management, electronic de-sign and delivery, a refined workflow, and an efficient management process.